KEKERASAN DALAM IMPLEMENTASI KELUARAGA BERENCANA (KB) TERHADAP PEREMPUAN DALAM PERSPEKTIF ISLAM - Robiatul Adawiyah (Al-'Adl, 2019)
The Family Planning grows rapidly in Indonesia as the implementation of government policy. This program has been planned to improve Indonesian people’s prosperity. The effectiveness of this program has been driven by the involvemen of government and society in communication, education and information (KEI). However, there is a tendency that the successful program conceals another side of the coin, that is gender inequality. This article tries to highlight women participation in this program which is motivated by an ideology impacting on their way of life. The different social status of man and woman which places women on subordinate position and sets them as the fragile one has made them become suspectible of violence, including on reproduction organs, which the use is of a matter of individual right. On the other side, religion and patriarchal culture play significan role in improving women participation in this Family Planning.